81.3.28 problem 28

Internal problem ID [18646]
Book : A short course on differential equations. By Donald Francis Campbell. Maxmillan company. London. 1907
Section : Chapter III. Ordinary differential equations of the first order and first degree. Exercises at page 33
Problem number : 28
Date solved : Tuesday, January 28, 2025 at 12:07:29 PM
CAS classification : [[_homogeneous, `class A`], _rational, _Riccati]

\begin{align*} 3 x^{2} y^{\prime }+2 x^{2}-3 y^{2}&=0 \end{align*}

Solution by Maple

Time used: 0.006 (sec). Leaf size: 26

dsolve((3*x^2)*diff(y(x),x)+(2*x^2-3*y(x)^2)=0,y(x), singsol=all)
 
\[ y \left (x \right ) = \frac {x \left (\sqrt {33}-11 \tanh \left (\frac {\left (\ln \left (x \right )+c_{1} \right ) \sqrt {33}}{6}\right )\right ) \sqrt {33}}{66} \]

Solution by Mathematica

Time used: 2.278 (sec). Leaf size: 101

DSolve[(3*x^2)*D[y[x],x]+(2*x^2-3*y[x]^2)==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to -\frac {x \left (\left (\sqrt {33}-3\right ) e^{\sqrt {33} c_1} x^{\sqrt {\frac {11}{3}}}-\sqrt {33}-3\right )}{6+6 e^{\sqrt {33} c_1} x^{\sqrt {\frac {11}{3}}}} \\ y(x)\to -\frac {1}{6} \left (\sqrt {33}-3\right ) x \\ y(x)\to \frac {1}{6} \left (3+\sqrt {33}\right ) x \\ \end{align*}